Early onset bilateral juvenile myasthenia gravis masquerading as simple congenital ptosis - Alam, Md. Shahid (GMS Ophthalmol Cases, 2017)
Myasthenia gravis is an autoimmune disorder affecting the neuromuscular junction. Ocular myasthenia gravis presents as ptosis with extraocular motility restriction and is prone to be misdiagnosed as third nerve palsy or congenital or aponeurotic ptosis. Juvenile ocular myasthenia gravis in very young children is difficult to diagnose and can be easily labeled as a case of congenital ptosis, the more so when the condition is bilateral. We present a case of a two-year-old child who presented with bilateral ptosis and was diagnosed as a case of simple congenital ptosis elsewhere with the advice to undergo tarsofrontalis sling surgery. The child was diagnosed with juvenile myasthenia gravis on thorough history, examination, and systemic evaluation and was started on anti-myasthenic treatment.